Hubungan Paritas Dengan Berat Badan Lahir Rendah (BBLR) - Elis Fatmawati; Dwi Retno Wati (Universitas Muhammadiyah Gresik, 2021)
One of the indicators that determine a country's health status is the high and low number of the Infant Mortality Rate (IMR). Meanwhile, the incidence of Low Birth Weight (LBW) is one of the main determining factors that contribute to the Infant Mortality Rate (IMR). Many factors cause an increase in the number of IMR, one of which is parity. This study aims to determine the relationship between parity and low birth weight (LBW) in Cendrawasih Dobo Hospital, Aru Islands Regency.This study uses analytical research with a